Addressing disparities and challenges in underserved patient populations with metastatic breast cancer in Europe. (February 2021) - Vrdoljak, Eduard; Gligorov, Joseph; Wierinck, Lieve; Conte, PierFranco; De Grève, Jacques; Meunier, Françoise; Palmieri, Carlo; Travado, Luzia; Walker, Andrew; Wiseman, Theresa; Wuerstlein, Rachel; Alba, Emilio; et al.
Abstract: People with metastatic breast cancer face many challenges and disparities in obtaining optimal cancer care. These challenges are accentuated in underserved patient populations across Europe, who are less likely to receive quality healthcare for reasons including socioeconomic inequalities, educational or cultural status, or geographic location. While there are many local and national initiatives targeted to address these challenges, there remains a need to reduce disparities and improve access to healthcare to improve outcomes, with a focus on multidisciplinary stakeholder engagement. In October 2019, a range of experts in metastatic breast cancer, including healthcare professionals, patient representatives, policymakers and politicians, met to discuss and prioritize the critical needs of underserved patient populations with metastatic breast cancer in Europe. Six key challenges faced by these communities were identified: the need for amplification of the metastatic breast cancer patient voice, better and wider implementation of high-quality guidelines for metastatic breast cancer, more collaboration between stakeholders, tailored support for patients from different cultural and ethnic backgrounds, improved data sharing, and work-related issues. The Expert Panel then conceived and discussed potential actionable goals to address each key challenge. Their conclusions present a set of interrelated approaches to address the different challenges and could serve as the basis for concerted improvement of the lives of patients with metastatic breast cancer in Europe. Highlights: A pan-European approach is needed to tackle disparities in metastatic breast cancer treatment. Multi-stakeholder collaboration may overcome challenges faced by underserved patients. New interventions integrated with existing initiatives could improve patient care.